Maslahah 'Ammah: (A Comparative Study of The Concept Maslahah 'Ammah According To Nahdlatul Ulama And Ulama Mazdhahib Al-Arba'ah) - al-Muthahhiri; M. Hasbi Umar; Ramlah (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The second similarity in terms of principles includes, a) paying attention to the realization of general welfare and benefit (maslahah 'âmmah) the welfare of national development in the life of the nation and state, b) rejecting damage and taking virtue (benevolence). As for the difference, it is stated that "maslahah 'âmmah may not sacrifice other public interests that are equal let alone bigger ones". In the view of al-madzhâhib al-Arbâ'ah did not mention in detail as in the view of NU. However, globally the Hanafiyah school of thought uses this concept of equality (qiyâs), that something that is the same is considered the same, let alone something more than that: it must be considered. Then there can be legal consequences more than commensurate (qiyâs awlawiyah). As for some of the three scholars (Mâlikiyah, Syafi'iyah, Hanâbilah) use istihsân, maslahah mursalah, sadz ad-Dari'ah and maslahah mulâ'im in bringing up maslahah 'âmmah and it is very clear that they do not mention anything in the same way - the same that can be taken as an equation (qiyâs) in realizing maslahah 'âmmah. The implications of the difference in the concept of maslahah 'âmmah are; a) will increase the breadth of the concept or make it easier to limit and seek decisions in the public interest (maslahah 'âmmah), in accordance with the development of the times which are increasingly rotating in the midst of life. Because in essence all of this boils down to one goal, namely the realization of maslahah 'âmmah (universal goodness), b) ijtihad produced by Nahdlatul Ulama, in realizing maslahah 'ammah and rejecting danger, is elastic in accordance with the times and conditions. Because the two concepts of NU and madzhâhib al-Arbâ'ah can complement or strengthen each other, c) the decisions made by NU are stronger. Because NU in formulating maslahah 'âmmah only adds or complements it. For example, the decision must be based on the provisions of syura (the voice of the government and the people).